Analysis of The Development of Russian Regional Entrepreneurship in The Condition of COVID-19 - Valery V. SMIRNOV; Vladislav L. SEMENOV; Anna N. ZAKHAROVA; Nina G. GUBANOVA; Tamara V. TALANOVA; Galina S. DULINA; Moris N. Yaklashkin (Communications of International Proceedings, 2021)
The article focuses on the crucial issues of current importance of the Russian regional entrepreneurship development in the conditions of business regulations change amid the COVID-19 pandemic. The notion of entrepreneurship is examined within the context of historical development and legal status to comprehend the essence of entrepreneurial activity and place of entrepreneurship in the Russian economy. Analysis of the entrepreneurship development in a lagging behind region of Russia resulted in the finding of its highest concentration related to small businesses turnover (micro businesses including) and at the same time keeping up population employment. The research found out an entrepreneurship trend to sell third party products reducing average headcount of staff in small businesses (micro businesses including).   Hierarchy of  small business economic activity kinds (micro businesses including) on the investment share into the fixed capital in turnover (as regards new and import fixed assets purchased) shows  nonremunerative investment support to "Agriculture, forestry, hunting, fishing, fish farming" and "Construction." Slowing down small business activity is earlier, deeper and more long-lasting in regard to sole proprietor activity. Small business development in a lagging behind region is possible only in the sphere of trade. The research enlarges the sphere of knowledge and develops abilities of the Russian Government officers to take system managerial decisions to allocate and reallocate investments.